If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3v + 8u + 8v + 9u = 0 Reorder the terms: 8u + 9u + 3v + 8v = 0 Combine like terms: 8u + 9u = 17u 17u + 3v + 8v = 0 Combine like terms: 3v + 8v = 11v 17u + 11v = 0 Solving 17u + 11v = 0 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-11v' to each side of the equation. 17u + 11v + -11v = 0 + -11v Combine like terms: 11v + -11v = 0 17u + 0 = 0 + -11v 17u = 0 + -11v Remove the zero: 17u = -11v Divide each side by '17'. u = -0.6470588235v Simplifying u = -0.6470588235v
| -5x+2=-1-2x | | f(x)=2x^2-5x+168 | | 4(2x+5)=3(x-6) | | -2n+9n-343=0 | | 10x-116=3x-11 | | 3a+5+(2a-3)= | | 7x+2+90+3x+-12=180 | | 6x+6+5x=50 | | 5x^2-29x=6 | | 3x-1=-7x+59 | | 4x+2-2x=-8 | | 5/3x+x=56 | | 12-5=n | | -3+3x=x-7 | | 7x+8=-7x+92 | | -a+3b-b+5a-6b= | | 5y+8=33 | | 10(x-8)=2x-20 | | 6=-3x+2x+5 | | 10-n=5 | | 33=x+7x+1 | | 60=-2(m+3)m | | 2x/x+4=8-8/x+4 | | 3(.75)=x | | 6x+5+5x=50 | | 12(2x-3)+5(7x-9)= | | 5x+1=-8 | | f(x)=2x^2-5x+3 | | -3-4(-1-x)=2 | | 41/5-35/6 | | y=-2/3x+3 | | 10(x-7)=7x-20 |